Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

Solve the initial value problem: x(dy/dx)+y(x) = 9y(x)^(2), y(1) = -1

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

\[x \frac{ dy }{dx } + y(x) = 9y(x)^2 , y(1) =-1\] Just the equation a little neater
I would solve for dy/dx and intergrate.
the ex's int he brackets are just indicating the independent variable right?\[x \frac{ \text dy }{\text dx } + y = 9y^2 , \]

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

and we know y(1) = -1.
I believe so, that's just how its been written. I'll try solving for dy/dx and integrating then,
So I would sub those in.
u realize that you can separate the variables easily here ?
\[\frac{ dy }{ dx } = \frac{ 9y(x)^2-y }{ x }\] Not too familiar with these problems, but basically i need to integrate that, no?
u bring all terms of one variable on one side of = sign, like this : \(\large \frac{1}{9y^2-y}dy=\frac{1}{x}dx\) then integrate
can u integrate both sides now ?
doing that now
take your time :)
think i got it, left an x over the y side so i confused my self. \[1 = \ln(1-9y)-\ln(y)\]
u integrated y-variable correctly , but what about \(\int (1/x)dx\) its not =1
i meant u should get something like this : \(\ln x=ln(1-9y)-lny+c\) then use logarithmic properties to simplify
Okay, catching on think i figured out what i did wrong when i integrated last anyway.
Maybe y = \[\frac{ 1 }{ x+9 }\] May be a final solution, just simplifying the equation?
ln cx= ln |(1-9y)/y| cxy= (1-9y) now use y(1) = -1 to find c.
u got this simplification ? ---->ln cx= ln |(1-9y)/y|
yup, \[C(-1)(1)=1-9(-1)\] \[-C=10\] \[C=-10\] \[10xy=(1-9y)\]
-10xy =1-9y or 10xy-9y+1=0
ahh, forgot the negative, think i have enough to try a few more of these questions any way. Thank you. :)
welcome ^_^

Not the answer you are looking for?

Search for more explanations.

Ask your own question